Pengaruh Tata Kelola Internal Terhadap Kinerja BUMD Provinsi Riau - Tica Darsa; Andreas Andreas; Kasman Arifin (Jurnal Akuntansi Keuangan dan Bisnis, 2015)
This research aimed to examine the effect of internal governance on company performance. With hope, good performance can improve the effectiveness and efficiency of the company so as to improve profitability and quality of local government owned enterprises.Data obtained through questionnaires filled out by the board of directors, audit committee, board of commissioner, managers and heads of divisions from local government-owned enterprises. There are 33 questionnaires that can be processed from 4 companies that participated in this research. The study used Structural Equation Model (SEM) and processed using SmartPLS version 2.0.From the test results of the four hypotheses showing that the entire hypothesis is accepted. They are The audit committee can affect the performance of the company; Internal audit can affect the performance of the company, Internal control can affect the performance of the company, and Internal governance can affect the performance of the company. Keywords: Internal governance, corporate performanc), and Partial Least Square (PLS)